Singular Integral Operators in Spaces of Oscillating Functions on a Rectifiable Curve - Plaksa, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We prove generalized Noether theorems for a singular integral equation with Cauchy kernel on a closed rectifiable Jordan curve in classes of piecewise-continuous functions with oscillation-type discontinuities. We obtain results concerning the normal solvability of operators associated with the equation and acting into a Banach space and incomplete normed spaces of piecewise-continuous oscillating functions.